Political Grammars : The Unconscious Foundations of Modern Democracy. - Tarizzo, Davide (Redwood City : Stanford University Press, 2021)
No detailed description available for "Political Grammars".
Cover -- Contents -- Foreword -- Preface -- Introduction. The Cartesian Connection -- Part I. Discourse and Grammar -- 1 The Clinical Approach to Political History -- 2 Emancipative Grammars: Laclau, Heller, and the People We Are -- 3 Human Properties: Villey, Macpherson, and Our Right to Be -- 4 Political Subjects: Lacan and Ordinary Ontologies -- Part II. Democracy and Fascism -- 5 The Freudian Paradigm of Critical Theory -- 6 The Two Paths to Modern Democracy -- 7 From Democracy to Fascism -- 8 Old and New Fascisms -- Conclusion. The Politics of Infinite Sets -- Notes -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Z.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Political science-Philosophy.; Fascism-Philosophy.; Democracy-Philosophy.; Subjectivity; Electronic books